Pengaruh Inflasi, Suku Bunga, Nilai Tukar dan Pertumbuhan GDP Terhadap Indeks Harga Saham : (Perusahaan Properti dan Real Estate Tahun 2017-2021) - Indah Devi Novian Sari; Emmelia Tan (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2023)
This study aims to analyze the factors that affect the stock price index of property and real estate companies listed on the Indonesia Stock Exchange (IDX) in 2017 - 2021. The factors tested in this study are Inflation, Interest Rates and Exchange Rates, and GDP Growth. Data obtained from yahoo finance, Central Statistics Agency, and Bank Indonesia. In this study, 60-month stock price index data was obtained. The analysis method used in this study is regression analysis and uses the Eviews 11 software program. This study uses the Classical Assumption Test, namely the Normality test, Multicollinearity test, Autocorrelation test, and Heteroscedasticity test. Hypothesis tests are Partial T test, Simultaneous F test, and Coefficient of Determination Test (R2). The results of the T pasrial test of this study show that inflation has a significant value (0.0404<0.05), interest rates have a significant value (0.0021<0.05), exchange rates have a significant value (0.0022<0.05), and GDP has a significant value (0.0026<0.05)